New dental graduates Satisfaction regarding acquired competencies during BDS course (Bangladesh Journal of Medical Education, 2014)
Objectives To assess the level of job satisfaction during BDS course among the new dental graduates according to their views including existing barriers and ways of further improvement. Materials and methods This was a cross sectional type of descriptive study and was carried out for one year. In depth interview were performed using interview schedule among twenty new dental graduates those were very interested and willing to participate in this study. Results Among them 96 new graduates were passed from non-government and 55in government dental colleges. Of them 53.3% were female and 46.7% were male. Satisfaction level on acquired competencies was not in desired level in Oral and maxillofacial surgery, orthodontics and some competencies in prosthodontics. Corresponding teacher, senior doctor and medical officer also by available patient and instrument and materials, good academic environment and good relation with teacher, causes much satisfaction. Main causes of dissatisfaction includes Less availability of the patients and instruments, lack of supervision and feedback in the clinical ward, insufficient practical classes and lack of competent instructors in all level. Conclusion New qualified dentists were more or less satisfied on their acquired competencies in most of the clinical areas. This may be due to having sufficient clinical exposure, experience and teaching time during their undergraduate course. There are several causes of satisfaction and so many causes of dissatisfaction. Co-operative and helpful teachers and senior doctors were very important issue for causing satisfaction. More teacher supervision and more patients for practice is recommended by them. DOI: http://dx.doi.org/10.3329/bjme.v2i2.18138 Bangladesh Journal of Medical Education Vol.2(2) 2011: 26-31